Multifunctional microneedle-mediated photothermo-gas-ion synergic therapy accelerates MRSA infacted diabetic wound healing - Shihao Deng; Yunhao Tai; Chenxu Liu; Kenan Sun; Shaoze Lan; Liu Yang; Canming Ye; Li Huang; Runhuai Yang; Haisheng Qian; Jun Li (Materials Today Bio)
Chronically high blood glucose levels in diabetic wounds form a complex microenvironment, and this microenvironment is represented by hypoxia, infection, and inflammation. Such an environment significantly impedes the wound healing cascade. Accordingly, monotherapeutic approaches have proven inadequate in addressing the complex nature of these wounds. Herein, we report the development of a reactive system comprising in situ generated glucose oxidase (GOx), Ta4C3 MXenes, and zinc sulfide nanoparticles (ZnS NPs). This system is integrated in a bilayer microneedle platform for sustained delivery. These microneedles facilitate synergistic photothermal therapy and PH responsive gas-ion therapy and also exhibit robust ROS scavenging properties. In addition, they demonstrate favorable mechanical characteristics and biocompatibility. Firstly, the inclusion of GOx effectively counteracts the negative effects of the high-sugar microenvironment. Secondly, the microneedles employ PH-responsive Zn2+, H2S release, and photothermal therapy to disrupt the structural integrity of Methicillin-Resistant Staphylococcus Aureus (MRSA) and dismantle the dense biofilm produced by this pathogen. The sustained release of MXenes offers broad-spectrum Reactive Oxygen Species (ROS) scavenging, and this process mitigates cellular apoptosis. In addition, these microneedles also enhance cell proliferation, migration, and angiogenesis in vitro effectively. Finally, in vivo studies utilizing type Ⅱ diabetic mice proved that these microneedles have photothermal antibacterial effectiveness and demonstrate their capacity to regulate inflammatory factors, promote angiogenesis and collagen deposition, and finally expedite tissue repair and regeneration, which offers a novel therapeutic strategy for the treatment of infected diabetic wounds.